The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment: a case of summer nutritional constraint? - Bugalho, Miguel N; Milne, John a (Forest Ecology and Management, 2003)
The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment, in southern Portugal, was estimated during summer 1995–1997 using n-alkane analysis. Standing crop of herbage layer biomass was estimated between June and September 1995–1997 using the clipping quadrat method. There was a large variability between years in the availability of the herbage layer biomass. Biomass was three fold greater and availability of legumes higher in a wet than in a dry year. Live green material was available in the herbage layer in June, but not thereafter, even during a wet year. Red deer ingested a higher proportion of browse in summer during drier years (0.83–0.89) than during a wet year (0.47). In the drier years, the herbage layer was replaced in the diet by browse species that were uneaten in the wet year. Contrary to Atlantic environments, where red deer include a large proportion of browse in their diets during winter, summer is likely to be a season of nutritional constraint for red deer inhabiting Mediterranean environments
Keywords: browse; cervus elaphus; diet composition; Mediterranean